2005
DOI: 10.2165/00128071-200506040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ceramides in Barrier Function of Healthy and Diseased Skin

Abstract: Stratum corneum intercellular lipids play an important role in the regulation of skin water barrier homeostasis and water-holding capacity. Modification of intercellular lipid organization and composition may impair these properties. Patients with skin diseases such as atopic dermatitis, psoriasis, contact dermatitis, and some genetic disorders have diminished skin barrier function. Lipid composition in diseased skin is characterized by decreased levels of ceramide and altered ceramide profiles. To clarify mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
143
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(149 citation statements)
references
References 61 publications
4
143
0
2
Order By: Relevance
“…In landdwelling animals, the skin permeability barrier prevents dehydration and electrolyte disturbances. This barrier is formed late in embryogenesis by tight junctions within the stratum granulosum and by layers of corneocytes embedded in a matrix of extracellular lipid lamellae (28)(29)(30)(31). The main components of the lipid matrix are Tg A+C /homozygous Stgd3 mice are smaller compared with their wt or heterozygous Stgd3 littermates, either Tg or nonTg.…”
Section: Discussionmentioning
confidence: 99%
“…In landdwelling animals, the skin permeability barrier prevents dehydration and electrolyte disturbances. This barrier is formed late in embryogenesis by tight junctions within the stratum granulosum and by layers of corneocytes embedded in a matrix of extracellular lipid lamellae (28)(29)(30)(31). The main components of the lipid matrix are Tg A+C /homozygous Stgd3 mice are smaller compared with their wt or heterozygous Stgd3 littermates, either Tg or nonTg.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramides are a structurally heterogeneous and complex group of sphingolipids containing derivatives of sphingosine bases in amide linkage with a variety of fatty acids with 24-26 carbon links. 4,32 Inside a cell, it has been reported that ceramides act as secondary signal transmitters and participate in the lipid signal paths in mammal cells, and induce cell proliferation and differentiation, restraint of cell cycle and apoptosis as major responses of intra-cell reaction to external stimulation. 33,34 Stratum corneum ceramides are heterogeneous compound mixtures.…”
mentioning
confidence: 99%
“…The major components of the stratum corneum lipids include ceramides, cholesterol and fatty acids, and it has been reported that they combine to form a multi-lamellar structure, and ceramides are major lipids that account for 40-50% of the stratum corneum lipids and play essential roles in the structure and function of the skin barrier. 32,36 Non-invasive methods of obtaining the stratum corneum lipids include in vivo surface extraction using organic solvents 37 and tape stripping. 38 In our study, we used cyanoacrylate stripping, 6 which involves applying cyanoacrylate resin on a glass slide and performing a single extraction of the horny layer, to obtain samples of the stratum corneum lipids.…”
mentioning
confidence: 99%
“…By mechanism of action, emollients are occlusive, humectant and/or restorative. Occlusive agents form a thin film on skin surface preventing moisture loss, mostly due to the presence of natural oils (Choi and Maibach, 2005;Bouwstra and Ponec, 2006). The use of emollients in topical products corrects problems in skin scaling disorders and emollients may also have suppressive effects on epidermal thickening, in addition to anti-inflammatory activity and transient relief from irritation (Nola et al, 2003).…”
Section: Discussionmentioning
confidence: 99%